Proceedings of the Twentieth Annual ACM-SIAM Symposium on Discrete Algorithms 2009
DOI: 10.1137/1.9781611973068.123
|View full text |Cite
|
Sign up to set email alerts
|

Paging and List Update under Bijective Analysis

Abstract: It has long been known that for the paging problem in its standard form, competitive analysis cannot adequately distinguish algorithms based on their performance: there exists a vast class of algorithms which achieve the same competitive ratio, ranging from extremely naive and inefficient strategies (such as Flush-When-Full), to strategies of excellent performance in practice (such as Least-Recently-Used and some of its variants). A similar situation arises in the list update problem: in particular, under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Bijective Analysis if there is a bijective mapping φ : S n → S n such that ALG 1 (σ ) ≤ ALG 2 (φ(σ )) for any σ ∈ S n . Very recently, Angelopoulos and Schweitzer [3] applied this idea to paging and showed that LRU is the unique optimal algorithm w.r.t. to Bijective Analysis for a restricted class of sequences exhibiting locality of reference.…”
Section: Other Measuresmentioning
confidence: 99%
“…Bijective Analysis if there is a bijective mapping φ : S n → S n such that ALG 1 (σ ) ≤ ALG 2 (φ(σ )) for any σ ∈ S n . Very recently, Angelopoulos and Schweitzer [3] applied this idea to paging and showed that LRU is the unique optimal algorithm w.r.t. to Bijective Analysis for a restricted class of sequences exhibiting locality of reference.…”
Section: Other Measuresmentioning
confidence: 99%
“…Such disconnects between the empirical and the theoretical performance evaluation have motivated a substantial line of research on measures alternative to the competitive ratio. Some of the known approaches are: the Max-Max ratio [11]; the diffuse adversary model [32,48,49]; loose competitiveness [47,50]; the random order ratio [30]; the relative worst-order ratio [15,14]; the accommodation function model [17]; and stochastic dominance as well as bijective and average analysis [28,18,19,42,36,34,3,25,4,5]. We refer the reader to the surveys [23,27] for an in-depth discussion of such techniques.…”
Section: Introductionmentioning
confidence: 99%
“…This latter notion was first introduced in [3] in the context of the paging problem and was shown to be consistent with some natural, "to-be-expected" properties of efficient online algorithms (e.g., the effect of locality of reference as well as lookahead) which competitive analysis fails to yield. For a further discussion of the appealing aspects of bijective analysis, see [3,5]. Definition 1 ( [3]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations